Positive electrode, method for preparing positive electrode, and lithium secondary battery comprising positive electrode
By lithiating the positive electrode surface of the lithium secondary battery and controlling the crack rate, and transferring the lithium metal layer to the positive electrode in combination with the transfer stack method, the heat and ignition problems caused by the reaction between lithium and silicon-type active materials are solved, and the heat and ignition problems are improved. Battery life and energy density.
Patent Information
- Application Number
- CN202380044725.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-08-11
- Publication Date
- 2024-12-31
AI Technical Summary
The reaction between existing lithium secondary batteries between lithium and silicon-based active materials leads to excessive heat and ignition risks, and the lithium prelithiation process is not conducive to battery life.
By lithiating the positive electrode surface, the crack rate of the positive electrode active material layer is controlled within the range of 5.0% to 14.2%, reducing the available area where lithium ions are embedded in the negative electrode, reducing the reaction area between lithium and silicon, and using the transfer stacking method to transfer lithium to the The metal layer is transferred to the positive electrode active material layer to avoid direct contact and move the lithium ions to the negative electrode when the battery is activated.
It effectively reduces the risk of alloying reaction between lithium and silicon and the reaction between lithium and water, extends the battery life, improves the energy density and capacity retention rate of lithium secondary batteries, and reduces the volume changes of negative electrodes.
Smart Images

Figure CN119234329A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the priority of Korean Patent Application No. 10-2022-0101636, filed on August 12, 2022, and Korean Patent Application No. 10-2022-0183744, filed on December 23, 2022, the disclosures of which are incorporated herein by reference. Technical Field
[0003] The present invention relates to an over-lithiated cathode, a method of preparing a cathode, and a lithium secondary battery including the cathode. Background Art
[0004] Due to the rapid increase in the use of fossil fuels, the demand for using alternative or clean energy has increased. As part of this trend, power generation and power storage using electrochemical reactions are the most active research fields.
[0005] Currently, typical examples of electrochemical devices using electrochemical energy can be secondary batteries, and their fields of use have a tendency to expand. In recent years, with the technological development and increasing demand for portable devices such as portable computers, mobile phones, and cameras, the demand for secondary batteries as an energy source has increased significantly. Among these secondary batteries, lithium secondary batteries with high energy density (i.e., high capacity) have been extensively studied and have been commercialized and widely used.
[0006] Generally, a secondary battery is composed of a cathode, an anode, an electrolyte, and a separator. The anode contains an anode active material in which lithium ions released from the cathode are intercalated and deintercalated, and silicon-based active material particles having a large discharge capacity can be used as the anode active material. The silicon-based active material particles can correspond to silicon (Si) or SiO x (0 < x < 2). The silicon-based active material particles have the advantages of large theoretical capacity and low price. However, since the silicon-based active material particles have an excessive volume change during battery operation, the disadvantage is that the battery life rapidly decreases as the battery is cycled.
[0007] Therefore, in order to minimize the volume change of silicon-based active material particles, there is a method of using only a portion of the total capacity of silicon-based active material particles. To this end, a so-called pre-lithiation process is used to embed lithium ions in a negative electrode containing silicon-based active material particles in advance. Specifically, if lithium ions are embedded in the negative electrode by, for example, transferring lithium metal to the negative electrode, the total capacity of the negative electrode can be reduced to the level of reversible capacity due to the reaction of lithium ions at irreversible sites of the negative electrode. Therefore, since the amount of embedded lithium ions during battery operation can be appropriately reduced to the level required for battery operation, the volume change of silicon-based active material particles can be minimized.
[0008] However, in the process of pre-lithiation by placing lithium metal on the surface of the negative electrode, excessive heat is generated due to the alloying reaction between lithium and silicon, and the possibility of fire due to the reaction between lithium and moisture is also increased. In addition, in the process of grooving and punching the negative electrode, the possibility of fire may be further increased due to the increase in the reaction area between lithium and silicon-based active materials, and there is also a serious safety problem due to the possibility of fire caused by pre-lithiation silicon-based active material particles.
[0009] Therefore, a new technology is needed that can suppress the possibility of excessive heat generation and fire while improving the life of the battery by pre-intercalating lithium ions into the negative electrode before the battery is operated. Summary of the invention
[0010] Technical issues
[0011] One aspect of the present invention provides a positive electrode, wherein the available area of the negative electrode can be controlled and the safety in the battery preparation process can be improved by overlithiation in the surface portion of the positive electrode to have a crack rate higher than a certain level; and a method for preparing the positive electrode.
[0012] Another aspect of the present invention provides a secondary battery in which life characteristics are improved due to control of a negative electrode usable area and unique characteristics of a negative electrode active material can be achieved without disadvantages by including a positive electrode.
[0013] Technical Solution
[0014] In order to solve the above problems, according to one aspect of the present invention, a positive electrode is provided, wherein the positive electrode comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises a positive electrode active material,
[0015] Here, the crack rate of the surface portion of the positive electrode active material layer obtained from Mathematical Formula 1 is in the range of 5.0% to 14.2%.
[0016] [Mathematical formula 1]
[0017] CR = (CA) / [(PA) + (CA)]
[0018] Here, CR is the crack rate (%), CA is the crack area, PA is the particle area, and the surface portion of the positive electrode active material layer refers to a region up to 20 μm from the layer surface in the depth direction.
[0019] In order to solve the above problems, according to another aspect of the present invention, a method for preparing a positive electrode is provided, the method comprising:
[0020] Step P1: disposing a transfer stack including a base film and a lithium metal layer disposed on the base film on the preliminary positive electrode active material layer to form a positive electrode structure, such that the lithium metal layer and the preliminary positive electrode active material layer are in contact with each other;
[0021] Step P2: rolling the positive electrode structure; and
[0022] Step P3: After calendering, the positive electrode is prepared by removing the base film from the transfer stack,
[0023] The positive electrode comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises a positive electrode active material, and
[0024] The crack rate of the surface portion of the positive electrode active material layer obtained from Mathematical Formula 1 is in the range of 5.0% to 14.2%.
[0025] In order to solve the above problem, according to another aspect of the present invention, a secondary battery is provided, wherein the secondary battery comprises a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode.
[0026] The positive electrode comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises a positive electrode active material, and
[0027] The crack rate of the surface portion of the positive electrode active material layer obtained from Mathematical Formula 1 is in the range of 5.0% to 14.2%.
[0028] Beneficial Effects
[0029] Since the positive electrode according to the present invention is over-lithiated by a specific method of lithium metal transfer, it has a certain level of crack rate in the surface portion. Accordingly, when lithium ions move to the negative electrode during the activation process, the life of the battery can be increased by reducing the available area of the negative electrode, and there is an advantage that the process risks caused by pre-lithiation of the negative electrode can be reduced.
[0030] In addition, by including the positive electrode, the secondary battery according to the present invention can increase the available area of the negative electrode, and accordingly, the capacity can be increased. In particular, in the case where a silicon-based negative electrode active material is used, only a portion of the available area can be used without losing lithium in the positive electrode due to overlithiation of lithium, and accordingly, there is an advantage that the life characteristics can be improved by minimizing the volume change. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a schematic diagram illustrating step P1 in a method for preparing a positive electrode according to one embodiment of the present invention.
[0032] Figure 2 is a schematic diagram illustrating step P1 of using a transfer stack including a polymer layer in the method for preparing a positive electrode according to one embodiment of the present invention.
[0033] Figure 3 is a schematic diagram illustrating step P2 in the method for preparing a positive electrode according to one embodiment of the present invention.
[0034] Figure 4 is a schematic diagram illustrating step P3 in the method for preparing a positive electrode according to one embodiment of the present invention. DETAILED DESCRIPTION
[0035] Hereinafter, the present invention will be described in more detail in order to more clearly understand the present invention.
[0036] It should be understood that, based on the principle that the inventor can appropriately define the meaning of words or terms to best explain the invention, the words or terms used in the specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it should also be understood that the words or terms should be interpreted as having meanings consistent with their meanings in the relevant technical context and the technical concept of the present invention.
[0037] The terms used herein are for the purpose of describing particular exemplary embodiments only and are not intended to limit the present invention.In the present specification, unless otherwise indicated, terms in the singular form may include plural forms.
[0038] It should also be understood that the terms “include,” “comprises,” or “has,” when used in this specification, specify the presence of the features, numbers, steps, elements, or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements, or a combination thereof.
[0039] In this manual, D 50 D can be defined as the particle size at which the cumulative volume is 50% in the particle size distribution curve. For example, D can be measured by using laser diffraction. 50Laser diffraction can routinely measure particle sizes from the submicron level to the millimeter range and can produce highly reproducible, high-resolution results.
[0040] positive electrode
[0041] The positive electrode according to the present invention comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises a positive electrode active material.
[0042] Here, the crack rate of the surface portion of the positive electrode active material layer obtained by the following Mathematical Formula 1 is in the range of 5.0% to 14.2%.
[0043] [Mathematical formula 1]
[0044] CR = (CA) / [(PA) + (CA)]
[0045] Here, CR is the crack rate (%), CA is the crack area, PA is the particle area, and the surface portion of the positive electrode active material layer refers to a region up to 20 μm from the layer surface in the depth direction.
[0046] According to one embodiment of the present invention, the positive electrode includes a positive electrode active material layer. The positive electrode active material layer itself can constitute the positive electrode, but the positive electrode active material layer can be provided on a positive electrode collector, and the positive electrode active material layer can be provided on one surface or both surfaces of the positive electrode collector.
[0047] According to one embodiment of the present invention, the positive electrode current collector is not particularly limited as long as it has conductivity without causing adverse chemical changes in the battery, and can use, for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. In addition, the thickness of the positive electrode current collector can generally be 3 μm to 500 μm, and fine concavoconvexity can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various shapes, such as a film, a sheet, a foil, a net, a porous body, a foam, a non-woven fabric, etc.
[0048] According to one embodiment of the present invention, the positive electrode active material is a material in the form of particles that can cause an electrochemical reaction, wherein it can be a lithium transition metal oxide. For example, the positive electrode active material can include at least one selected from the following: a layered compound substituted by at least one transition metal, such as lithium cobalt oxide or lithium nickel oxide; a lithium manganese oxide substituted by at least one transition metal; 1+x [Ni a Co b Mn c M 1 (1-a-b-c) ]O (2-d) Ad The represented lithium nickel cobalt manganese composite oxide (where M 1 is at least one selected from aluminum (Al), magnesium (Mg), chromium (Cr), titanium (Ti), silicon (Si), and yttrium (Y), A is at least one selected from fluorine (F), phosphorus (P), and chlorine (Cl), -0.5 ≤ x ≤ 0.5, 0.1 ≤ a ≤ 1, 0.05 ≤ b ≤ 0.5, 0.05 ≤ c ≤ 0.5, 0 ≤ d ≤ 0.2 and 0 < a + b + c ≤ 1); the lithium nickel-based oxide represented by Li[Ni 1-y M 2 y O2 (where M 2 can be at least one selected from cobalt (Co), manganese (Mn), Al, copper (Cu), iron (Fe), Mg, boron (B), Cr, zinc (Zn), and gallium (Ga), 0.01 ≤ y ≤ 0.7); and the olivine-type lithium metal phosphate represented by Li 1+z [M 3 1-q M 4 q PO 4-r X r (where M 3 is at least one selected from Fe, Mn, Co, and nickel (Ni), M 4 is at least one selected from Al, Mg, and Ti, X is at least one selected from F, sulfur (S), and nitrogen (N), -0.5 ≤ z ≤ 0.5, 0 ≤ q ≤ 0.5, 0 ≤ r ≤ 0.1).
[0049] Specifically, the positive electrode active material may include a layered structured lithium nickel-based transition metal composite oxide. The lithium nickel-based transition metal composite oxide may include a compound of the following Chemical Formula 1, and more specifically, may be a compound of the following Chemical Formula 1.
[0050] [Chemical Formula 1]
[0051] Li 1+x [Ni a Co b Mn c M 1 (1-a-b-c) O (2-d) A d
[0052] In Chemical Formula 1,
[0053] M 1 is at least one selected from Al, Mg, Cr, Ti, Si, and Y. Specifically, it may be Al.
[0054] A is at least one selected from F, P, and Cl. Specifically, it may be F.
[0055] x can satisfy -0.5 ≤ x ≤ 0.5, specifically, -0.3 ≤ x ≤ 0.3.
[0056] a can satisfy 0.6 ≤ a < 1, specifically, 0.7 ≤ a ≤ 0.9.
[0057] b can satisfy 0.03 ≤ b ≤ 0.1, specifically, 0.05 ≤ b ≤ 0.1.
[0058] c can satisfy 0.03 ≤ c ≤ 0.1, specifically, 0.05 ≤ c ≤ 0.1.
[0059] d can satisfy 0 ≤ d ≤ 0.1, specifically, 0 ≤ d ≤ 0.05.
[0060] a, b, and c satisfy 0 < a + b + c ≤ 1, specifically, a + b + c = 1.
[0061] The compound of Formula 1 can be in the form of particles.
[0062] The compound of Formula 1 can be in the form of secondary particles, wherein a plurality of primary particles are combined with each other. Specifically, the compound of Formula 1 can be in the form of secondary particles, wherein more than 10 primary particles are combined with each other. Therefore, there is an effect that lithium can be uniformly inserted into and deintercalated from the positive electrode active material.
[0063] D of the compound of Formula 1 50 can be 5 μm to 15 μm, particularly 7 μm to 12 μm, more particularly 9 μm to 10 μm. D 50 can be the D of the secondary particles 50 . Since the positive electrode paste is easily dispersed when the above range is satisfied, the positive electrode active material layer can be uniformly coated.
[0064] In the positive electrode active material layer, the content of the positive electrode active material can be 90% by weight to 99% by weight, particularly 92% by weight to 98% by weight, more particularly 95% by weight to 98% by weight.
[0065] According to one embodiment of the present invention, the positive electrode active material layer may further include a positive electrode binder. The positive electrode binder improves the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples of binders may be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof may be used.
[0066] In the positive electrode active material layer, the positive electrode binder may be contained in an amount of 0.5 wt % to 5.0 wt %, specifically 1.0 wt % to 2.5 wt %, and more specifically 1.0 wt % to 2.0 wt %.
[0067] According to one embodiment of the present invention, the positive electrode active material layer may further include a positive electrode conductive material. The positive electrode conductive material is used to provide conductivity to the electrode, wherein any conductive material may be used without particular limitation, as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. Specific examples of positive electrode conductive materials may be graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; powders or fibers of metals such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof may be used.
[0068] In the positive electrode active material layer, the content of the positive electrode conductive material may be 0.5 wt % to 30.0 wt %, specifically 0.5 wt % to 10.0 wt %, and more specifically 1.0 wt % to 4.0 wt %.
[0069] According to one embodiment of the present invention, the positive electrode is characterized in that a crack rate of a surface portion of the positive electrode active material layer given by the following Mathematical Formula 1 is in a range of 5.0% to 14.2%.
[0070] [Mathematical formula 1]
[0071] CR = (CA) / [(PA) + (CA)]
[0072] Here, CR is the crack rate (%), CA is the crack area, PA is the particle area, and the surface portion of the positive electrode active material layer refers to a region up to 20 μm from the layer surface in the depth direction.
[0073] For the crack rate, the cross section of the positive electrode is analyzed, so that the area of 20 μm in the depth direction and 200 μm in the in-plane direction from the surface of the active material layer is set as a reference area, and the crack area and the particle area are divided in the area to obtain the area. The crack area is the part where the particles are broken, and the particle area is the area where the particles are not broken, wherein the electrode is cut by ion milling and the cut section is photographed with a scanning electron microscope (SEM). For the SEM cross-sectional image, the crack area and the particle area are quantified based on digital conversion, wherein the ratio of the area with increased specific surface area in the positive electrode is calculated and quantified by an additional process. In addition, in order to improve the accuracy, more than 50 reference areas are specified for the positive electrode cross section to obtain the crack rate of each area, and the average value thereof is obtained.
[0074] According to one embodiment of the present invention, the crack rate may be in the range of 5.0% to 14.2%, preferably 6.0% or more, 7.0% or more, 8.0% or more, or 9.0% or more, and may be 14.1% or less or 14.0% or less. A crack rate of less than 5.0% means that the lithium ions in the positive electrode active material layer are not sufficiently over-lithiated, wherein, since there is not enough lithium to move to the negative electrode through activation, it may be difficult to increase the available area of the negative electrode, resulting in problems such as negative electrode volume expansion that may reduce life characteristics.
[0075] That is, in the preparation process of the positive electrode of the present invention, the lithium metal layer is transferred to the positive electrode active material layer, and then the positive electrode containing the lithium metal layer is rolled, so that the lithium ions of the lithium metal layer are embedded in the positive electrode active material layer. In this process, the lithium ions generate lithium by-products. Therefore, a crack rate of 5.0% or more can be considered to mean that the lithium metal layer is transferred to the positive electrode active material layer and the positive electrode is rolled in the process of preparing the positive electrode of the present invention.
[0076] If the crack rate is greater than 14.2%, the capacity of the positive electrode active material decreases, and side reactions due to broken particles may increase battery resistance or gas generation, resulting in performance degradation. Therefore, in the case where overlithiation is performed to control the available area of the negative electrode, it is necessary to make the crack rate meet a specific range through appropriate control.
[0077] According to one embodiment of the present invention, the positive electrode may further include a lithium metal layer disposed on the positive electrode active material layer. The lithium metal layer serves to supply lithium ions to the positive electrode active material layer. Specifically, the positive electrode active material layer may be disposed between the positive electrode current collector and the lithium metal layer. The lithium metal layer may be in contact with the positive electrode active material layer. The lithium metal layer includes solid-phase lithium metal, and the lithium metal layer may be specifically formed of solid-phase lithium metal. Through transfer and rolling, the lithium metal layer may undergo solid-phase diffusion of metallic lithium into the positive electrode active material layer, and therefore, after activation, the lithium metal layer may not exist, or may exist in a state where its thickness is extremely thin.
[0078] According to one embodiment of the present invention, the positive electrode may further include a polymer layer disposed on the positive electrode active material layer. During the preparation of the positive electrode, the polymer layer may effectively peel off the lithium metal layer from the transfer stack and easily transfer the lithium metal layer to the positive electrode active material layer. That is, the polymer layer may be separated from the transfer stack together with the lithium metal layer to be disposed on the positive electrode active material layer. The polymer layer may be present in contact with the positive electrode active material layer, or the lithium metal layer may be present between the polymer layer and the positive electrode active material layer.
[0079] The polymer layer may be at least one selected from polyethylene terephthalate (PET), polyimide (PI), poly(methyl methacrylate) (PMMA), polypropylene, polyethylene and polycarbonate. Therefore, in a secondary battery comprising a positive electrode, since the polymer layer can be dissolved in the electrolyte contained in the secondary battery, the battery resistance can be prevented from increasing. In particular, the polymer layer may include PMMA, in which case the above-mentioned effect can be further improved.
[0080] According to one embodiment of the present invention, in the positive electrode, the porosity of the positive electrode active material layer may be 10% to 40%, particularly 15% to 35%, and more particularly 25% to 30%. In this case, no additional thickness change occurs during calendering.
[0081] In the positive electrode according to one embodiment of the present invention, a lithium metal layer is provided on the positive electrode by a transfer method, and the lithium of the lithium metal layer is intercalated into the positive electrode active material layer by solid phase diffusion by rolling. During battery operation, lithium can move to the negative electrode, thereby reducing the available area of the negative electrode.
[0082] Therefore, since the available range of the negative electrode capacity can be reduced without losing lithium in the positive electrode active material due to the over-lithiation of lithium in the positive electrode, the excessive volume change of the silicon-based active material can be suppressed and the life characteristics of the battery can be improved. In addition, since the capacity of the positive electrode active material can be used in the entire range, there is an advantage of improving battery efficiency and maximizing energy density.
[0083] The positive electrode according to one embodiment of the present invention is characterized in that pre-lithiation is not performed by typically contacting a lithium metal layer with a negative electrode, but by transferring a lithium metal layer to the positive electrode and rolling it, and then transferring lithium ions embedded in the positive electrode to the negative electrode during battery activation.
[0084] That is, since the negative electrode is not in contact with the lithium metal layer and the lithium ions are not directly embedded in the negative electrode from the lithium metal layer, the phenomenon of excessive heat generation due to the alloying reaction of lithium and silicon at the negative electrode can be avoided, and the possibility of fire due to the reaction between lithium and moisture can be significantly reduced. In addition, since the lithium ions are not embedded in the negative electrode during the process of grooving and punching the negative electrode (because no pre-lithiation is performed), the possibility of fire during the grooving and punching process can be significantly reduced.
[0085] <Method for Preparing Positive Electrode>
[0086] The method for preparing a positive electrode according to the present invention comprises:
[0087] Step P1: disposing a transfer stack including a base film and a lithium metal layer disposed on the base film on the preliminary positive electrode active material layer to form a positive electrode structure, such that the lithium metal layer and the preliminary positive electrode active material layer are in contact with each other;
[0088] Step P2: rolling the positive electrode structure; and
[0089] Step P3: After calendering, the positive electrode is prepared by removing the base film from the transfer stack,
[0090] The positive electrode comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, and
[0091] The crack rate of the surface portion of the positive electrode active material layer obtained from the following Mathematical Formula 1 is in the range of 5.0% to 14.2%.
[0092] [Mathematical formula 1]
[0093] CR = (CA) / [(PA) + (CA)]
[0094] Here, CR is the crack rate (%), CA is the crack area, PA is the particle area, and the surface portion of the positive electrode active material layer refers to a region up to 20 μm from the layer surface in the depth direction.
[0095] According to one embodiment of the present invention, step P1 of the method for preparing a positive electrode is a step of disposing a transfer stack including a base film and a lithium metal layer on the preliminary positive electrode active material layer to form a positive electrode structure so that the lithium metal layer and the preliminary positive electrode active material layer are in contact with each other.
[0096] Reference Figure 1 , the transfer stack 300 may include a base film 310 and a lithium metal layer 320 disposed on the base film 310. The base film 310 may be used without limitation as long as it is a material that can withstand the high temperature conditions present during the deposition of the lithium metal layer 320 on the base film 310. Specifically, the base film may include at least one selected from polyethylene terephthalate (PET), polyimide (PI), poly(methyl methacrylate) (PMMA), polypropylene, polyethylene, and polycarbonate.
[0097] According to one embodiment of the present invention, a lithium metal layer may be provided on the base film. The lithium metal layer serves to supply lithium ions to the preliminary positive electrode active material layer. The lithium metal layer contains solid-phase lithium metal, and the lithium metal layer may be specifically formed of solid-phase lithium metal.
[0098] According to one embodiment of the present invention, in the transfer stack, the thickness of the lithium metal layer can be 1.0 μm to 10.0 μm, specifically, the thickness can be 2.0 μm or more, 2.5 μm or more, or 3.0 μm or more, and the thickness can also be 9.5 μm or less, 9.0 μm or less, 8.5 μm or less, 8.0 μm or less, 7.5 μm or less, 7.0 μm or less, or 6.5 μm or less. In the case where the above range is met, since the degree of cracks of the positive electrode active material particles on the surface of the positive electrode can be reduced to a point where it does not affect the performance and application of available lithium, that is, the amount of lithium loss can be controlled to be low, therefore, due to compensating the irreversible capacity of the negative electrode, the initial capacity of the battery can be suppressed from decreasing and the life can be improved.
[0099] According to one embodiment of the present invention, the loading amount of the lithium metal layer (unit: mAh / cm 2 ) can be the loading amount of the prepared positive electrode active material layer (unit: mAh / cm 2 ), specifically 12% to 35%, and more specifically 20% to 30%. When the above range is met, since the generation of by-products is small and lithium can be easily embedded in the positive electrode active material, the target lithium embedding capacity can be easily achieved.
[0100] In step P1, refer to Figure 1 , a preliminary positive active material layer 120 ′ is disposed on the positive current collector 110 , and a transfer stack 300 may be disposed on the preliminary positive active material layer 120 ′ to form a positive electrode structure 400 , such that the lithium metal layer 320 and the preliminary positive active material layer are in contact with each other.
[0101] Herein, since the positive electrode current collector 110 has been described above in the description of the positive electrode, the description thereof will be omitted.
[0102] Reference Figure 2 , the transfer stack 300 may further include a polymer layer 330. The polymer layer 330 may be disposed between the base film 310 and the lithium metal layer 320. During the preparation of the positive electrode, the polymer layer may effectively peel off the lithium metal layer from the transfer stack and easily transfer the lithium metal layer to the positive electrode active material layer. That is, the polymer layer may be separated from the transfer stack together with the lithium metal layer to be disposed on the positive electrode active material layer. The polymer layer may be present in contact with the positive electrode active material layer, or the lithium metal layer may be present between the polymer layer and the positive electrode active material layer.
[0103] Herein, since the polymer layer has been described above in the description of the positive electrode, the description thereof will be omitted.
[0104] The thickness of the polymer layer may be 0.1 μm to 10 μm, particularly 0.5 μm to 5 μm, and more particularly 1 μm to 2.5 μm. In the case where the above range is satisfied, the lithium metal layer may be easily transferred to the positive electrode active material layer, and a reverse transfer phenomenon in which the positive electrode active material layer is transferred to the transfer stack may be prevented.
[0105] According to one embodiment of the present invention, step P2 of the method for preparing a positive electrode is a step of rolling the positive electrode structure.
[0106] Reference Figure 3 , in step P2, the prepared positive electrode structure 400 can be calendered. The calendering can be performed by a calendering method. Specifically, by two rollers R spaced apart from each other by a predetermined space in the vertical direction, pressure can be applied to the positive electrode structure 400 passing through the space in the vertical direction, and the pressure can be a linear pressure. Through the calendering process, at least a portion of the lithium ions of the lithium metal layer contained in the transfer stack can be embedded in the prepared positive electrode active material layer. In this process, the prepared positive electrode active material layer can become the positive electrode active material layer. In Figure 3 and Figure 4 In , the lithium metal layer included in the positive electrode is illustrated, but in the case where the entire lithium metal layer is embedded in the preliminary positive electrode active material layer during the rolling process, the lithium metal layer may not exist as a separate layer.
[0107] The pressure applied to the positive electrode structure during the calendaring process may be in the range of 10 to 90 kgf / cm, specifically 15 to 80 kgf / cm, and more specifically 20 to 40 kgf / cm.
[0108] In the case where the rolling pressure within the above range is applied, the lithium metal layer can be effectively transferred, and lithium can be embedded in the positive electrode at a desired level. An appropriate level of crack rate can also be met. Therefore, the effect of satisfying both life improvement and capacity characteristics can be achieved.
[0109] According to one embodiment of the present invention, step P3 of the method for preparing a positive electrode is a step of preparing a positive electrode by removing the base film from the transfer stack after calendaring.
[0110] Reference Figure 4 In step P3, the positive electrode 100 may be prepared by removing the base film 310 from the transfer stack after the calendering performed in step P2. In the case where the polymer layer 330 is disposed between the base film 310 and the lithium metal layer 320, the base film 310 may be more easily removed by the polymer layer 330.
[0111] In addition, according to one embodiment of the present invention, the method for preparing a positive electrode may further include step P4, allowing the prepared positive electrode to stand (place) for 1 minute to 600 minutes, specifically 1 minute to 30 minutes. Step P4 can be performed after step P2. Specifically, step P4 can be performed in at least one step of 'between step P2 and step P3' and 'immediately after step P3'. Since the reaction heat generated by the reaction of the lithium metal layer with the prepared positive electrode active material layer in step P2 can be effectively released through step P4, the lithium is uniformly embedded in the positive electrode, so there is an effect of reducing the generation of by-products.
[0112] In addition, since the prepared positive electrode has been described previously, its description will be omitted.
[0113] Secondary battery
[0114] The secondary battery according to the present invention comprises a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode.
[0115] The positive electrode comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises a positive electrode active material, and
[0116] The crack rate of the surface portion of the positive electrode active material layer obtained by the following Mathematical Formula 1 is in the range of 5.0% to 14.2%.
[0117] [Mathematical formula 1]
[0118] CR = (CA) / [(PA) + (CA)]
[0119] Here, CR is the crack rate (%), CA is the crack area, PA is the particle area, and the surface portion of the positive electrode active material layer refers to a region up to 20 μm from the layer surface in the depth direction.
[0120] Since the positive electrode has been described above, its description will be omitted.
[0121] According to an embodiment of the present invention, the negative electrode includes a negative electrode active material layer, the negative electrode active material layer may include a negative electrode active material, and a silicon-based negative electrode active material, a carbon-based negative electrode active material, or a combination thereof may be used as the negative electrode active material.
[0122] According to an embodiment of the present invention, the negative electrode active material may include a silicon-based negative electrode active material. The silicon-based negative electrode active material may include at least one of Si and SiO x (0 < x < 2).
[0123] Si is silicon particles, where it may be silicon particles (particles formed of silicon), so-called pure silicon. The silicon particles can effectively improve the capacity of the negative electrode. SiO x (0 < x < 2) may be in a form including Si and SiO2, and Si may form a phase. That is, x corresponds to the number ratio of oxygen (O) to Si contained in SiO x (0 < x < 2). In the case where the silicon-based composite particles include SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.
[0124] According to an embodiment of the present invention, the silicon-based negative electrode active material has a problem of extremely poor life characteristics due to a large volume change during battery operation. However, in the case where it is combined with the positive electrode according to the present invention, since excessive lithium ions (rather than the lithium that determines the capacity in the positive electrode active material) transfer from the over-lithiated positive electrode to the silicon-based negative electrode active material and react with the silicon-based negative electrode active material in advance during activation, an irreversible phase is formed, thereby reducing the available area. Therefore, the volume change during battery operation is not serious, so that the life can be significantly improved, and the high-capacity characteristics can be fully realized, which is an inherent characteristic of the silicon-based negative electrode active material.
[0125] According to an embodiment of the present invention, the negative electrode active material may further include a carbon-based negative electrode active material. The carbon-based negative electrode active material may include at least one selected from artificial graphite, natural graphite, and graphitized mesophase carbon microbeads.
[0126] According to one embodiment of the present invention, the negative electrode active material layer may further include a negative electrode binder. The negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylate, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials whose hydrogen is replaced by lithium (Li), sodium (Na) or calcium (Ca), or various copolymers thereof may be included.
[0127] According to one embodiment of the present invention, the negative electrode active material layer may further include a negative electrode conductive material. There is no particular limitation on the negative electrode conductive material, as long as it has conductivity and does not cause adverse chemical changes in the battery, for example, the following conductive materials may be used, such as: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers or metal fibers; conductive tubes, such as carbon nanotubes; fluorocarbons; metal powders, such as aluminum powders and nickel powders; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxides; or polyphenylene derivatives.
[0128] According to one embodiment of the present invention, the secondary battery includes a separator. The separator separates the negative electrode from the positive electrode and provides a mobile path for lithium ions, wherein any separator can be used as a separator without particular limitation, as long as it is commonly used in secondary batteries, in particular, preferably a separator having high water retention capacity for electrolytes and low resistance to electrolyte ion transfer. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure having two or more layers thereof. In addition, a typical porous nonwoven fabric can be used, for example, a nonwoven fabric formed by high melting point glass fiber or polyethylene terephthalate fiber. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be optionally used.
[0129] According to one embodiment of the present invention, the secondary battery may further include an electrolyte. The electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte or a molten inorganic electrolyte that can be used to prepare a lithium secondary battery, but the present invention is not limited thereto.
[0130] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt. Examples of non-aqueous organic solvents may include aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0131] Especially, in carbonate organic solvent, ethylene carbonate and propylene carbonate, cyclic carbonate are owing to the high dielectric constant as high viscosity organic solvent and dissociate the lithium salt in the electrolyte well, therefore can preferably use cyclic carbonate.Because cyclic carbonate can prepare the electrolyte with high conductivity when mixing with suitable ratio with the straight-chain carbonate of low viscosity, low dielectric constant of for example dimethyl carbonate and diethyl carbonate.Therefore can more preferably use cyclic carbonate.
[0132] A lithium salt may be used as the metal salt, and the lithium salt is a material that is easily soluble in the non-aqueous electrolyte, wherein, for example, at least one selected from the following may be used as an anion of the lithium salt: - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2- 、SCN - and (CF3CF2SO2)2N - .
[0133] In order to improve the life characteristics of the battery, inhibit the decline of the battery capacity and improve the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, the electrolyte may also contain at least one additive, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.
[0134] As described above, since the secondary battery including the cathode according to the present invention stably exhibits excellent capacity and capacity retention, the secondary battery is suitable for portable devices such as mobile phones, notebook computers, and digital cameras; and electric vehicles such as hybrid electric vehicles (HEVs).
[0135] Therefore, according to another embodiment of the present invention, there are provided a battery module including a secondary battery as a unit cell and a battery pack including the battery module.
[0136] The battery module and the battery pack may be used as a power source for at least one medium or large device selected from the following: a power tool; an electric vehicle (EV); a hybrid electric vehicle; a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0137] Example
[0138] Preferred embodiments will be provided below to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are provided only to illustrate the present invention, and various modifications and changes are possible within the scope and technical spirit of the present invention. These modifications and changes fall within the scope of the claims included herein.
[0139] Electrode preparation
[0140] Example 1-1: Preparation of positive electrode
[0141] A transfer stack was prepared, which included a PET film (base film), a polymer layer (2.5 μm thick) formed of PMMA disposed on the PET film, and a lithium metal layer (3.0 μm thick, with a loading of 0.62 mAh / cm) disposed on the polymer layer and formed of solid-phase lithium metal. 2 ).
[0142] Using Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 as the positive electrode active material. The positive electrode active material is a plurality (more than 10) of Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 primary particles are in the form of secondary particles bonded to each other, and the average particle size of the secondary particles is D 50 The positive electrode was prepared, the positive electrode comprising a preliminary positive electrode active material layer and an aluminum foil (thickness: 12 μm) as a positive electrode current collector, the preliminary positive electrode active material layer comprising a positive electrode active material, PVdF as a positive electrode binder, and carbon nanotubes as a positive electrode conductive material in a weight ratio of 98:1:1. The loading capacity of the preliminary positive electrode active material layer was 4.5 mAh / cm 2 , the thickness is 140 μm.
[0143] The transfer stack is disposed on the preliminary positive electrode active material layer so that the lithium metal layer is in contact with the preliminary positive electrode active material layer.
[0144] Thereafter, the positive electrode on which the transfer stack is disposed is rolled by a rolling method and then left to stand for 24 hours. The pressure during rolling is 20 kgf / cm. Thus, the lithium ions of the lithium metal layer can be embedded in the prepared positive electrode active material layer to form a positive electrode active material layer. Thereafter, the base film is removed and the rolled positive electrode is left to stand for 10 minutes to prepare a positive electrode comprising a positive electrode collector, a positive electrode active material layer and a polymer layer.
[0145] Example 1-2: Preparation of positive electrode
[0146] The positive electrode was prepared in the same manner as in Example 1-1, except that the thickness of the lithium metal layer was 6.2 μm and the loading amount was 1.28 mAh / cm 2 .
[0147] Example 1-3: Preparation of positive electrode
[0148] A positive electrode was prepared in the same manner as in Example 1-2, except that the rolling pressure was 30 kgf / cm.
[0149] Comparative Example 1-1: Preparation of positive electrode
[0150] A positive electrode was prepared in the same manner as in Example 1-1, except that the transfer stack was not used.
[0151] Comparative Example 1-2: Preparation of positive electrode
[0152] The positive electrode was prepared in the same manner as in Example 1-1, except that the thickness of the lithium metal layer was 11.6 μm and the loading amount was 1.90 mAh / cm 2 .
[0153] Comparative Example 1-3: Preparation of positive electrode
[0154] A positive electrode was prepared in the same manner as in Example 1-2, except that the rolling pressure was 100 kgf / cm.
[0155] Experimental Example 1: Evaluation of the physical properties of the positive electrode
[0156] For the positive electrodes prepared in Example 1-1 to Example 1-3 and Comparative Example 1-1 to Comparative Example 1-3, the crack rate (%) was measured by the following method.
[0157] One day after each positive electrode was prepared, the cross section of the positive electrode was analyzed, so that the area of 20 μm from the surface of the active material layer in the depth direction and 200 μm in the in-plane direction was set as the reference area, and the crack area and the particle area were divided in the area to obtain the area. The crack area is a part where the particles are broken, and the particle area is an area where the particles are not broken, wherein the cross section of the electrode is cut by ion milling, and photographed with a scanning electron microscope (SEM) to obtain an image.
[0158] For SEM cross-sectional images, the crack area and particle area are quantified based on digital conversion, where the ratio of the area with increased specific surface area in the positive electrode is calculated and quantified through an additional process. In addition, in order to improve accuracy, more than 50 reference areas are specified for the positive electrode cross section to obtain the crack rate of each area and obtain its average value.
[0159]
[0160] As shown in Table 1, for Examples 1-1 to 1-3, it can be confirmed by the crack rate that lithium is inserted into the positive electrode by overlithiation, and Comparative Example 1-1 confirms that the crack rate is different between the overlithiation case and the non-overlithiation case. For Comparative Example 1-2, the lithium layer is too thick during lithium transfer, and for Comparative Example 1-3, it can be confirmed that the degree of cracking of the positive electrode active material particles is too high as a result of a slight increase in the rolling pressure.
[0161] Preparation of secondary batteries
[0162] Example 2-1: Preparation of secondary battery
[0163] Average particle size D 50The negative electrode was prepared by using 5 μm silicon particles as the negative electrode active material. The negative electrode included a preliminary negative electrode active material layer, the preliminary negative electrode active material layer including the negative electrode active material, carboxymethyl cellulose (CMC) as a negative electrode binder, and carbon nanotubes as a negative electrode conductive material in a weight ratio of 80:10:10. The loading capacity of the preliminary negative electrode active material layer was 10 mAh / cm 2 , the thickness is 75 μm.
[0164] The positive electrode, negative electrode and porous polyethylene separator of Example 1-1 were assembled using a winding method, and a preliminary lithium-ion secondary battery was prepared by injecting electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio) and lithium hexafluorophosphate (LiPF6 1 mol) into the assembled battery.
[0165] The prepared lithium ion secondary battery was charged to 4.2 V at a C rate of 0.1 C and then discharged to 2.5 V to perform an activation process.
[0166] Example 2-2 and Example 2-3: Preparation of secondary battery
[0167] Lithium ion secondary batteries were prepared in the same manner as in Example 2-1, except that the positive electrodes of Example 1-2 and Example 1-3 were used instead of the positive electrode of Example 1-1, respectively.
[0168] Comparative Examples 2-1 to 2-3: Preparation of Secondary Batteries
[0169] Lithium ion secondary batteries were prepared in the same manner as in Example 2-1, except that the positive electrodes of Comparative Examples 1-1 to 1-3 were respectively used instead of the positive electrode of Example 1-1.
[0170] Experimental Example 2: Initial Efficiency Evaluation
[0171] For the lithium secondary batteries of Example 2-1 to Example 2-3 and Comparative Example 2-1 to Comparative Example 2-3, initial efficiency was evaluated under the following conditions.
[0172] Charging conditions: CC (constant current) / CV (constant voltage) (5 mV / 0.005 C current cutoff) 4.2 V
[0173] Discharge condition: CC (constant current) condition 2.5 V
[0174]
[0175] Referring to Table 2, for Comparative Example 2-1, it can be understood that due to the low crack rate of the positive electrode active material particles, the initial efficiency is excellent, but the initial charge capacity is significantly low, which may be due to the difference caused by the presence or absence of over-lithiation. In addition, for Comparative Example 2-2, over-lithiation was performed, but the degree was too high, so a high initial charge capacity was exhibited, and it can be confirmed that the effect may be reduced due to the large amount of lithium loss caused by the irreversible capacity that was not restored to the discharge capacity. Similar to Comparative Example 2-2, Comparative Example 2-3 also has a high initial capacity due to over-lithiation, but it can be understood that due to the small recovered capacity, the lithium loss is large. On the contrary, for Examples 2-1 to 2-3, the initial capacity is increased by supplementing lithium through over-lithiation, and it can be confirmed that due to the small lithium loss, the capacity can be used at a higher level than the comparative example.
[0176] Experimental Example 3: Evaluation of life characteristics of secondary batteries
[0177] Each of the secondary batteries of Examples 2-1 to 2-3 and Comparative Examples 2-1 to 2-3 was charged and discharged using the following method to evaluate the life characteristics of the secondary batteries, and the results are presented in Table 3 below.
[0178] * Life characteristics (capacity retention rate): Each secondary battery was charged and discharged at 0.1 C in the first cycle and the second cycle, and was charged and discharged at 0.5 C in the third cycle to the 100th cycle.
[0179] Charging conditions: CC (constant current) / CV (constant voltage) (5 mV / 0.005 C current cutoff) 4.2 V
[0180] Discharge condition: CC (constant current) condition 3.27 V
[0181] Each capacity retention rate was obtained by the following calculation.
[0182] Capacity retention rate (%) = (Nth discharge capacity / 1st discharge capacity) × 100 (where N is 500 and 800)
[0183]
[0184] Referring to Table 3, it can be confirmed that the life characteristics of Examples 2-1 to 2-3 are better than those of Comparative Examples 2-1 to 2-3. For Comparative Example 2-1, since the crack rate of the positive electrode active material particles is low, excellent initial charge and discharge characteristics are exhibited, but since the available area of the negative electrode is not limited, the battery deteriorates due to the volume expansion of the negative electrode, so it can be confirmed that the life characteristics are poor, and since Comparative Examples 2-2 and 2-3 have high crack rates, it can be confirmed that the life is reduced due to the side reaction with the electrolyte. In addition, for the embodiment, the capacity retention rate at 800 cycles is maintained at about 75% of the capacity retention rate at 500 cycles, but for the comparative example, it can be understood that even the level of 70% cannot be maintained. Therefore, it can be understood that since the capacity retention rate itself is lower, the life of the comparative example is shorter, but it can be understood that the rate of capacity degradation of the comparative example is also faster.
[0185] [reference numerals]
[0186] 110: Positive electrode collector
[0187] 120, 120': preparing positive electrode active material layer
[0188] 300: Transfer stack
[0189] 310: Base film
[0190] 320: Lithium metal layer
[0191] 330: Polymer layer
[0192] 400: Positive electrode structure
[0193] R: Roller
Claims
1. A positive electrode, comprising a positive electrode active material layer, wherein the positive electrode active material layer comprises a positive electrode active material, in, The crack rate of the surface portion of the positive electrode active material layer is in the range of 5.0% to 14.2% obtained from Mathematical Formula 1: [Mathematical formula 1] CR = (CA) / [(PA) + (CA)] Here, CR is a crack rate (%), CA is a crack area, PA is a particle area, and the surface portion of the positive electrode active material layer refers to a region up to 20 μm from the layer surface in the depth direction. 2 . The positive electrode according to claim 1 , further comprising a lithium metal layer provided on the positive electrode active material layer. 3 . The positive electrode according to claim 1 , further comprising a polymer layer provided on the positive electrode active material layer.
4. The positive electrode according to claim 1, wherein The crack rate of the surface portion of the positive electrode active material layer is in the range of 6.0% to 14.1%.
5. The positive electrode according to claim 1, wherein The crack rate of the surface portion of the positive electrode active material layer is in the range of 7.0% to 14.0%.
6. The positive electrode according to claim 1, wherein The positive electrode active material is at least one selected from lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel composite oxide, lithium manganese composite oxide and lithium transition metal phosphate.
7. A method for preparing a positive electrode, the method comprising: Step P1: disposing a transfer stack including a base film and a lithium metal layer disposed on the base film on the preliminary positive electrode active material layer to form a positive electrode structure, so that the lithium metal layer and the preliminary positive electrode active material layer are in contact with each other; Step P2: rolling the positive electrode structure; and Step P3: after the calendering, preparing a positive electrode by removing the base film from the transfer stack, wherein the positive electrode comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, and The crack rate of the surface portion of the positive electrode active material layer is in the range of 5.0% to 14.2% obtained from Mathematical Formula 1: [Mathematical formula 1] CR = (CA) / [(PA) + (CA)] Here, CR is a crack rate (%), CA is a crack area, PA is a particle area, and the surface portion of the positive electrode active material layer refers to a region up to 20 μm from the layer surface in the depth direction.
8. The method according to claim 7, wherein: The calendering in step P2 is performed by a roll-to-roll method.
9. The method according to claim 7, wherein: The thickness of the lithium metal layer is 1 μm to 10 μm.
10. The method according to claim 7, wherein: The loading amount of the lithium metal layer is 4% to 40% of the loading amount of the preliminary positive electrode active material layer.
11. The method according to claim 7, wherein: The transfer stack further comprises a polymer layer, and The polymer layer is disposed between the base film and the lithium metal layer.
12. The method according to claim 7, further comprising after step P2: Step P4: allowing the prepared positive electrode to stand for 1 minute to 600 minutes.
13. The method according to claim 7, wherein: The pressure applied to the positive electrode structure during the rolling is in a range of 10 kgf / cm to 90 kgf / cm.
14. A lithium secondary battery, comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, in, The positive electrode comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, and The crack rate of the surface portion of the positive electrode active material layer is in the range of 5.0% to 14.2% obtained from Mathematical Formula 1: [Mathematical formula 1] CR = (CA) / [(PA) + (CA)] Here, CR is a crack rate (%), CA is a crack area, PA is a particle area, and the surface portion of the positive electrode active material layer refers to a region up to 20 μm from the layer surface in the depth direction.
15. The lithium secondary battery according to claim 14, wherein: The negative electrode comprises a negative electrode active material layer, and the negative electrode active material layer comprises a negative electrode active material, Wherein, the negative electrode active material comprises a silicon-based negative electrode active material.
